Five- to 7-Year-Olds’ Finger Gnosia and Calculation Abilities - Reeve, Robert (Frontiers in Psychology, 2011)
The research examined the relationship between 65 5- to 7-year-olds’ finger gnosia, visuo-spatial working memory and finger-use solving single digit addition problems. Their non-verbal IQ and basic RT were also assessed. Previous research has found significant changes in children’s representational abilities between five and seven years. One aim of the research was to determine whether changes in finger representational abilities (finger gnosia) occur across these ages and whether they are associated with finger-use in computation. A second aim was to determine whether visuo-spatial working memory is associated with finger gnosia and computation abilities. We used latent class profile analysis to identify patterns of similarities and differences in finger gnosia and computation/finger-use abilities. The analysis yielded four finger gnosia subgroups that differed in finger representation ability. It also yielded four finger/computation subgroups that differed in the relationship between finger-use and computation success. Analysis revealed associations between computation finger-use/success subgroups, finger gnosia subgroups, and visuo-spatial working memory. A multinomial logistic regression analysis showed that finger gnosia subgroup membership and visuo-spatial working memory uniquely contribute to a model predicting finger-use in computation group membership. The results show that finger gnosia abilities change in the early school years, and that these changes are associated with the ability to use fingers to aid computation.